Optimal Model of Operation Parameters of Gathering Pipeline Network with Triple-Line Process. (28th March 2013) - Liang, Yongtu; Lu, Cen; Ren, Kuijie; Xiao, Qiao; He, Guoxi
Abstract : This is a mathematic model for the optimal operation of the gathering pipeline network and its solution provides this gathering pipeline network having a triple-line heat-tracing process, a method for reducing the operational costs and increasing economic benefit. The model consists of an objective function, minimum total operation cost, and 3 constraints including water temperature constraint at pipe nodes, inlet oil temperature constraints, and outlet water temperature constraint. By using a sequential quadratic programming algorithm, the model can be solved and a set of optimal mass rate and the desired temperature of tracing water are attained. The method is here specifically applied to the optimal operation analysis of a gathering pipeline network in North China Oilfield. The result shows its operation cost can be reduced by 2076RMB/d, which demonstrates that this method contributes to the production cost reduction of old oilfields in their high water-cut stage.